Iron-based phosphate positive electrode material and preparation method and application thereof

Through the integrated solid-liquid preparation method, metal iron reacts with phosphorus sources to form a solid-liquid mixture, and is treated with acid regulator, carbon source and sodium source, which solves the problems of impurities and long process in the prior art, and realizes efficient and low-cost iron-based phosphate positive electrode material preparation, which is suitable for the industrial application of sodium ion batteries.

CN119812287AActive Publication Date: 2025-04-11NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202510232154.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-27
Publication Date
2025-04-11
Estimated Expiration
2045-02-27

AI Technical Summary

Technical Problem

Electrochemically inert impurities are easily generated during the synthesis of existing sodium ion battery iron-based phosphate cathode materials, and the existing preparation methods rely on expensive grinding equipment, and the process flow is lengthy and not suitable for large-scale production.

Method used

The solid-liquid integrated preparation method is adopted to form a solid-liquid mixture by reacting metal iron and phosphorus source at room temperature ~ 100°C, and sand-milling and drying are combined with an acid regulator, a carbon source and a sodium source. Finally, sintering is carried out under a protective atmosphere to obtain the iron-based phosphate positive electrode material.

Benefits of technology

It significantly shortens the production cycle, reduces the difficulty of subsequent processing, improves the activity and performance of materials, is suitable for industrial production and large-scale production, and has environmentally friendly processes and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812287A_ABST
    Figure CN119812287A_ABST
Patent Text Reader

Abstract

The invention provides an iron-based phosphate positive electrode material as well as a preparation method and application thereof. The preparation method of the positive electrode material comprises the following steps: reacting a mixed material containing metallic iron and a phosphorus source at normal temperature to 100 DEG C to form a solid-liquid mixture containing a phosphate iron salt compound; mixing the solid-liquid mixture with an acidity regulator, a carbon source and a sodium source, and sanding to obtain slurry; performing drying treatment on the slurry to obtain a precursor material; and sintering the precursor material under a protective atmosphere condition to obtain the iron-based phosphate positive electrode material. According to the method provided by the invention, the metal iron and the phosphorus source do not need to be mixed and completely dissolved to form a solution in the reaction process, and anhydrous iron phosphate does not need to be formed firstly, so that the method for preparing the iron-based phosphate positive electrode material is short in process and relatively low in requirements on reaction conditions, and is applicable to industrial production and large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy technology, and specifically relates to an iron-based phosphate positive electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have received widespread attention in recent years due to their abundant resources, low cost and broad application prospects. In the research on key cathode materials for sodium-ion batteries, improving energy density, cycle stability and rate performance is the current main research direction. Common cathode materials include polyanion compounds, layered oxides and Prussian blue compounds. Among them, although layered oxides have a high specific capacity, their cycle stability is poor; Prussian blue analogs are prone to introduce crystal water during the synthesis process, resulting in structural instability and affecting cycle performance. In contrast, polyanion compounds have become an ideal choice for sodium-ion battery cathode materials due to their stable crystal structure and efficient sodium ion transport channels.

[0003] Among polyanionic compounds, phosphate cathode materials have attracted much attention due to their good balance between low cost and high capacity. Typical materials include vanadium-based compounds (Na3V2(PO4)3, Na3V2(PO4)2F3), manganese-based compounds Na3MnTi(PO4)3, etc.) and iron-based compounds (NaFePO4, Na4Fe3(PO4)2P2O7), etc. Among them, sodium iron pyrophosphate is considered to be a highly promising cathode material for large-scale energy storage systems due to its high theoretical specific capacity, low raw material cost, simple synthesis process and excellent cycle performance. However, its synthesis process is easily accompanied by the electrochemically inert sodium iron phosphate ore-type NaFePO4, and the presence of this impurity will significantly reduce the electrochemical performance of the material. In addition, the existing preparation methods usually rely on expensive grinding equipment and require long working hours to reduce the crystallinity and particle size of the material, resulting in large equipment investment, high energy consumption, and lengthy process flow, which is not conducive to large-scale production.

[0004] Therefore, developing a preparation process for high-purity sodium iron pyrophosphate and exploring efficient and low-cost synthesis methods have become the focus of current research. This will not only help improve the electrochemical performance of the material, but will also promote the commercial application of sodium-ion batteries in the field of large-scale energy storage.

[0005] At present, the iron-based phosphate positive electrode materials of sodium ion batteries usually use iron salts such as ferric nitrate and ferric phosphate as raw materials. In the prior art, CN118867197A discloses a method for preparing sodium iron pyrophosphate positive electrode materials using ferrous phosphate, ferric phosphate, ferrous nitrate, ferrous oxalate or ferrous carbonate as iron sources; CN119008875A discloses a method for preparing sodium iron phosphate positive electrode materials using at least two iron sources of ferric nitrate, ferric sulfate, ferric acetate, ferric chloride, ferric citrate, ferric tartrate and ferric tribromide. However, these methods have many limitations in practical applications: compared with the most common iron phosphate route in industrialization, it is first necessary to react iron salts with phosphoric acid, and anhydrous iron phosphate is obtained through precipitation, neutralization of pH value and drying. Moreover, since iron phosphate needs to be treated by aging, high-temperature annealing and dehydration, it has high crystallinity, and the energy barrier for conversion to sodium iron pyrophosphate phase is high, and it is easy to produce impurities, which is not conducive to the efficient synthesis of materials. For example, when ferric nitrate is used as the iron source, nitrogen oxides will be produced during the preparation process, which will harm human health and environmental safety. In addition, the production costs of ferrous oxalate and ferrous phosphate are relatively high, which is difficult to meet the needs of industrialization. Although iron oxide is low in cost, its purity is low and it often contains impurities, making it difficult to control product consistency. Summary of the invention

[0006] In order to solve all or part of the above-mentioned technical problems, the present invention proposes an innovative "solid-liquid integration" preparation idea. This method directly enters the next step by generating a solid-liquid mixture, without the need to prepare anhydrous iron phosphate in advance, thereby significantly shortening the production cycle. In addition, this method has the advantages of short reaction process, small product particle size, low hardness, etc., which reduces the difficulty of subsequent processing. At the same time, since a solid-liquid mixture is formed with low crystallinity and high activity, it is easier to obtain high-performance target materials. This invention not only simplifies the process flow, but also improves the material properties, providing a new solution for the industrialization of iron-based phosphate positive electrode materials for sodium ion batteries. Accordingly, the present invention provides the following technical solutions:

[0007] One of the purposes of the present invention is to provide a method for preparing an iron-based phosphate positive electrode material, comprising:

[0008] The mixed material containing metallic iron and phosphorus source is reacted at room temperature to 100° C. to form a solid-liquid mixture containing an iron phosphate compound;

[0009] The solid-liquid mixture is mixed with an acidic regulator, a carbon source and a sodium source, and then sand-milled to obtain a slurry;

[0010] Drying the slurry to obtain a precursor material;

[0011] The precursor material is sintered under protective atmosphere conditions to obtain an iron-based phosphate positive electrode material.

[0012] The composition of the iron phosphate compounds formed by the reaction of metallic iron and phosphorus source is relatively complex, including one or more of Fe3(PO4)2, FePO4, FeHPO4, Fe3(PO4)2(OH)2, etc. and their hydrates, and also includes hydroxyphosphates, such as one or more of stilbite Fe3(PO4)2(OH)2, magnesite Fe5(PO4)4(OH)2·2H2O, rock bridge iron Fe5(PO4)3(OH)5, Fe4(PO4)3(OH)3, etc.

[0013] In some embodiments, the method specifically includes: mixing the metallic iron and the phosphorus source in a molar ratio of 1 to 1.75:2 to 2.25, and reacting at room temperature to 100° C. for 6 h to 12 h to form the iron phosphate compound, thereby obtaining the solid-liquid mixture.

[0014] In some embodiments, the phosphorus source includes one or a combination of phosphoric acid, sodium dihydrogen phosphate, and ferrous dihydrogen phosphate.

[0015] In some embodiments, the metallic iron includes one or a combination of iron blocks, iron sheets, and iron powder.

[0016] In some embodiments, the acidic regulator includes one or a combination of oxalic acid, tartaric acid, and citric acid.

[0017] In some embodiments, the carbon source includes glucose.

[0018] In some embodiments, the molar ratio of the acidic regulator to the iron element is 1:5 to 1:7.5.

[0019] In some embodiments, according to the chemical formula Na 3-4.5 Fe 2-3.5 (PO4) 2-2.5 P2O7 supplements the sodium source to the solid-liquid mixture.

[0020] In some embodiments, the amount of the carbon source added satisfies a molar ratio of the carbon source to iron of 1:10 to 1:15.

[0021] In some embodiments, the method specifically includes: mixing the solid-liquid mixture with an acidic regulator, a carbon source, a sodium source and polyethylene glycol and then performing the sand milling, wherein the amount of polyethylene glycol added is 1 / 400 to 1 / 600 of the total mass of the slurry.

[0022] In some embodiments, the method specifically includes: the sand grinding is performed at a temperature of 20 to 30° C. and the sand grinding time is 2 h to 4 h, so that the particle size of the particles in the slurry is 500 to 600 nm.

[0023] In some embodiments, the drying is spray drying, and the inlet temperature of the spray drying is 210-250°C, and the outlet temperature is 100-105°C.

[0024] In some embodiments, the protective atmosphere is at least one of argon and nitrogen; or, the protective atmosphere is an argon-hydrogen mixed gas or a nitrogen-hydrogen mixed gas, and the volume proportion of hydrogen in the argon-hydrogen mixed gas or the nitrogen-hydrogen mixed gas is 5% to 10%.

[0025] In some embodiments, the sintering specifically includes: firstly raising the temperature to 290-310°C at a rate of 1.5-2.5°C / min and keeping it warm for 2.5-3.5h, and then raising the temperature to 500-550°C at a rate of 1.5-2.5°C / min and keeping it warm for 8-10h.

[0026] A second object of the present invention is to provide an iron-based phosphate positive electrode material, which is prepared by any of the methods described above.

[0027] The third object of the present invention is to provide a sodium ion battery positive electrode, which includes a current collector and a positive electrode active material layer formed on the current collector, and the positive electrode active material layer includes the iron-based phosphate positive electrode material.

[0028] A fifth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode is the positive electrode of the sodium ion battery.

[0029] Compared with the prior art, the present invention has at least the following beneficial effects:

[0030] (1) The present invention provides a method for preparing an iron-based phosphate positive electrode material based on a solid-liquid mixture formed by metallic iron and a phosphorus source. During the reaction process, there is no need to mix the metallic iron and the phosphorus source and completely dissolve them to form a solution, nor is there a need to first form anhydrous iron phosphate. This is a method for preparing an iron-based phosphate positive electrode material in a short process. Compared with the method in the prior art that requires first preparing soluble Fe(H2PO4)2 and anhydrous iron phosphate, the method provided by the present invention has a short process and lower requirements on reaction conditions. It is a method suitable for industrial production and large-scale production.

[0031] (2) Since the solid-liquid mixture has low crystallinity and high activity, it is easier to obtain high-performance target materials. The prepared iron-based phosphate positive electrode material has high activity, small particle size and low hardness. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0033] Figure 1 It is a charge and discharge curve diagram of the positive electrode material prepared in Example 1 of the present invention.

[0034] Figure 2 It is a charge and discharge curve diagram of the positive electrode material prepared in Example 2 of the present invention.

[0035] Figure 3 It is a charge and discharge curve diagram of the positive electrode material prepared in Example 3 of the present invention.

[0036] Figure 4a , Figure 4b This is a SEM image of the positive electrode material prepared in Example 2 of the present invention.

[0037] Figure 5 It is the XRD image of the positive electrode material prepared in Examples 1 and 2 of the present invention. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is described in detail below in conjunction with specific embodiments so that those skilled in the art can better understand and implement the technical solution of the present invention. The specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0039] In addition, unless otherwise specified, the various raw materials used in the following examples can be purchased from the market and other channels, and the various production and testing equipment used are also equipment known in the art.

[0040] Example 1

[0041] This embodiment provides a method for preparing a high-purity sodium ion battery phosphate positive electrode material using metallic iron, comprising the following specific steps:

[0042] (1) 81.2 g of metallic iron powder and 230.2 g of phosphoric acid (concentration of 85 wt%) were placed in a beaker, and 1 L of deionized water was added, and the mixture was reacted in a water bath at 80° C. for 8 h to form a solid-liquid mixture containing iron phosphate compounds such as Fe3(PO4)2(OH)3, Fe3(PO4)2, FePO4, and FeHPO4;

[0043] (2) The solid-liquid mixture was placed in a sand mill, and 27 g of oxalic acid and 30 g of glucose were added and sand milled. The sand milling temperature was 25° C. and the rotation speed was 2000 rpm. After sand milling for 2 h, 106 g of sodium carbonate was added and sand milling was continued for 2 h to obtain a light yellow slurry.

[0044] (3) spray drying the light yellow slurry obtained above, wherein the inlet temperature of the spray drying is 220° C., the outlet temperature is 100° C., and the feed rate is set to 2 L of slurry per hour, thereby obtaining a precursor material;

[0045] (4) The precursor material is placed in a tubular furnace for sintering. Under the condition of introducing a hydrogen-argon mixed atmosphere (hydrogen volume accounts for 5%), the temperature is first increased to 300°C at a rate of 2°C / min and kept warm for 3 hours, and then the temperature is increased to 500°C at a rate of 2°C / min and kept warm for 10 hours. The chemical formula of the obtained product is Na4Fe3(PO4)2P2O7.

[0046] Example 2

[0047] This embodiment provides a method for preparing a high-purity sodium ion battery phosphate positive electrode material using metallic iron, comprising the following specific steps:

[0048] (1) 82.08 g of metallic iron powder and 230.2 g of phosphoric acid (concentration of 85 wt%) were placed in a beaker, and 1 L of deionized water was added, and the mixture was fully reacted in a water bath at 80° C. for 8 h to form a solid-liquid mixture containing iron phosphate compounds such as Fe3(PO4)2(OH)3, Fe3(PO4)2, FePO4, and FeHPO4;

[0049] (2) putting the obtained solid-liquid mixture into a sand mill, adding 18 g of oxalic acid and 30 g of glucose, and then sand milling the mixture. The sand milling temperature is 20° C. and the speed is 1800 rpm. After 2 h, 106 g of sodium carbonate is added, and the sand milling is continued for 2 h to obtain a light yellow slurry.

[0050] (3) spray drying the light yellow slurry obtained above, with the spray drying inlet temperature at 250° C., the outlet temperature at about 105° C., and the feed rate at about 2 L of slurry per hour to obtain a precursor material;

[0051] (4) The precursor material was placed in a tube furnace for sintering. Under the condition of introducing a hydrogen-argon mixed atmosphere (hydrogen volume ratio is 10%), the temperature was first raised to 190°C at a rate of 1.5°C / min and kept warm for 2.5 hours, and then the temperature was raised to 520°C at a rate of 1.5°C / min and kept warm for 8 hours. The chemical formula of the obtained product was Na4Fe 2.91 (PO4)2P2O7.

[0052] Example 3

[0053] This embodiment provides a method for preparing a high-purity sodium ion battery phosphate positive electrode material using metallic iron, comprising the following specific steps:

[0054] (1) 81.2 g of metal iron sheet and 230.2 g of phosphoric acid (concentration of 85 wt%) were placed in a beaker, and 1 L of deionized water was added, and the mixture was fully reacted in a water bath at 100° C. for 6 h to form a solid-liquid mixture containing iron phosphate compounds such as Fe3(PO4)2(OH)3, Fe3(PO4)2, FePO4, and FeHPO4;

[0055] (2) The obtained solid-liquid mixture was placed in a sand mill, and 30 g of tartaric acid and 30 g of glucose were added and sand milled. The sand milling temperature was 30° C. and the rotation speed was 2200 rpm. After sand milling for 2 h, 108.5 g of sodium carbonate was added and sand milling was continued for 2 h to obtain a light yellow slurry.

[0056] (3) spray drying the light yellow slurry obtained above, with the spray drying inlet temperature at 210° C., the outlet temperature at about 100-105° C., and the feed rate at about 2 L of slurry per hour to obtain a precursor material;

[0057] (4) The precursor material was placed in a tube furnace for sintering. Under the condition of introducing a hydrogen-argon mixed atmosphere (hydrogen volume ratio is 8%), the temperature was first raised to 310°C at a rate of 2.5°C / min and kept warm for 3.5 hours, and then the temperature was raised to 550°C at a rate of 2.5°C / min and kept warm for 10 hours. The chemical formula of the obtained product was Na 4.1 Fe3(PO4)2P2O7.

[0058] Example 4

[0059] (1) 81.2 g of iron particles with a particle size of 2.5 mm and 312.02 g of NaH2PO4·2H2O were placed in a basket sand mill, 1 L of deionized water was added, and the mixture was sand milled in the basket sand mill for 8 h to react, with the temperature of the grinding chamber being controlled at 50° C. and the rotation speed being controlled at 1200 rpm to form a slurry;

[0060] (2) The slurry prepared above was placed in a sand mill, and 38.4 g of citric acid and 30 g of glucose were added and sand milled. The sand milling temperature was 25° C. and the speed was 2000 rpm. After sand milling for 2 h, 53 g of sodium carbonate was added and sand milling was continued for 2 h to obtain a light yellow slurry.

[0061] (3) spray drying the light yellow slurry obtained above, with the spray drying inlet temperature at 220° C., the outlet temperature at about 100° C., and the feed rate at about 2 L of slurry per hour, thereby obtaining a precursor material;

[0062] (4) The precursor material is placed in a tubular furnace for sintering. Under the condition of introducing a hydrogen-argon mixed atmosphere (hydrogen volume accounts for 5%), the temperature is first increased to 300°C at a rate of 2°C / min and kept warm for 3 hours, and then the temperature is increased to 500°C at a rate of 2°C / min and kept warm for 10 hours to obtain an iron-based phosphate positive electrode material.

[0063] Example 5

[0064] The only difference between Example 5 and Example 1 is that the atmosphere used in the sintering process of step (4) is pure argon, and the rest is implemented in the same way as Example 1 and will not be repeated here.

[0065] Comparative Example 1

[0066] Comparative Example 1 The positive electrode material is prepared by a conventional method, and the specific steps are as follows:

[0067] (1) 209.5 g of ferrous oxalate was reacted with 230.2 ml of phosphoric acid solution (with a concentration of 85 wt%) to obtain Fe(H2PO4)2, and then Fe(H2PO4)2 was reacted with 300 ml of hydrogen peroxide (with a concentration of 30 wt%) to obtain a dihydrate ferric phosphate precursor, and anhydrous ferric phosphate was obtained by dehydration. The anhydrous ferric phosphate, 30 g of glucose, 27 g of oxalic acid and 1000 ml of deionized water were added to a sand mill for sand milling at a temperature of 30° C. and a rotation speed of 2200 rpm. After sand milling for 2 h, 106 g of sodium carbonate was added, and sand milling was continued for 2 h to obtain a light yellow slurry;

[0068] (3) spray drying the light yellow slurry obtained above, with the spray drying inlet temperature at 220° C., the outlet temperature at about 100° C., and the feed rate at about 2 L slurry per hour to obtain a precursor material;

[0069] (4) The precursor material was placed in a tube furnace for sintering. Under the condition of introducing a hydrogen-argon mixed atmosphere (hydrogen volume ratio is 5%), the temperature was first raised to 310°C at a rate of 2.5°C / min and kept warm for 3.5 hours, and then the temperature was raised to 550°C at a rate of 2.5°C / min and kept warm for 10 hours. The chemical formula of the obtained product was Na 4.1 Fe3(PO4)2P2O7. Grind into a uniform slurry, then dry and sinter to obtain the finished product.

[0070] The positive electrode for sodium ion battery was prepared using the phosphate positive electrode material prepared in the above embodiment and comparative example as a raw material, specifically:

[0071] The sodium ion battery was assembled using the positive electrode prepared above, the negative electrode was Na foil, the electrolyte was DC / EC / EMC+2%FEC (DoDo Chem, Shanghai, China) dissolved with NaClO4 as electrolyte, and the separator was a glass fiber membrane (GF / A What-man). The relevant properties of the obtained sodium ion battery positive electrode were tested, and the test structure is shown in Table 1.

[0072] Figure 1 It is the charge and discharge curve diagram of the positive electrode material prepared in Example 1. Figure 2 This is a charge and discharge curve diagram of the positive electrode material prepared in Example 2. Figure 3 It is the charge and discharge curve diagram of the positive electrode material prepared in Example 3. Figure 4a , Figure 4b This is a SEM image of the positive electrode material prepared in Example 2 of the present invention. Figure 5 It is the XRD image of the positive electrode material prepared in Examples 1 and 2 of the present invention.

[0073] Table 1 Relevant performance of sodium ion batteries

[0074] Group Charge capacity Discharge specific capacity First effect Example 1 115.1mAh / g 99.4mAh / g 86.3% Example 2 117.1mAh / g 102.4mAh / g 87.4% Example 3 115.2mAh / g 98.2mAh / g 85.2% Example 4 114.8mAh / g 98.7mAh / g 85.9% Example 5 114.8mAh / g 98.7mAh / g 85.9% Comparative Example 1 113.2mAh / g 98.2mAh / g 86.7%

[0075] The method provided by the present invention uses metallic iron, and no oxidant, catalyst, etc. need to be added during the reaction process, which helps to improve production capacity and effectively reduce the introduction of impurities. The prepared sodium ion battery iron-based phosphate positive electrode material has high purity and excellent performance in charge and discharge performance such as capacity utilization, rate, and cycle life. The method uses abundant metallic iron as an iron source, avoids the use of expensive raw materials such as organic salt compounds, and has high resource utilization. The method can directly prepare positive electrode materials from metallic iron without the use of precursors such as iron phosphate, has a short process, low process cost, and the performance of the prepared positive electrode material is equivalent to that of Comparative Example 1; no wastewater, waste residue, or harmful gas is generated during the preparation process, which meets the requirements of green and sustainable development.

[0076] The various aspects, embodiments, features and examples of the present invention should be considered as illustrative in all aspects and are not intended to limit the present invention, the scope of the present invention is defined only by the claims. Other embodiments, modifications and uses will be apparent to those skilled in the art without departing from the spirit and scope of the claimed invention.

[0077] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0078] Although the present invention has been described with reference to illustrative embodiments, it will be appreciated by those skilled in the art that various other changes, omissions and / or additions may be made without departing from the spirit and scope of the present invention and that the elements of the embodiments may be replaced by substantial equivalents. In addition, many modifications may be made without departing from the scope of the present invention to adapt specific circumstances or materials to the teachings of the present invention. Therefore, it is not intended herein to limit the present invention to the disclosed specific embodiments for performing the present invention, but it is intended that the present invention will include all embodiments within the scope of the appended claims. In addition, unless specifically stated, any use of the terms first, second, etc. does not indicate any order or importance, but rather uses the terms first, second, etc. to distinguish one element from another.

Claims

1. A method for preparing an iron-based phosphate positive electrode material, characterized in that: include: The mixed material containing metallic iron and phosphorus source is reacted at room temperature to 100° C. to form a solid-liquid mixture containing an iron phosphate compound; The solid-liquid mixture is mixed with an acidic regulator, a carbon source and a sodium source, and then sand-milled to obtain a slurry; Drying the slurry to obtain a precursor material; The precursor material is sintered under protective atmosphere conditions to obtain an iron-based phosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: Specifically include: The metallic iron and the phosphorus source are mixed in a substance molar ratio of 1 to 1.75:2 to 2.25, and reacted at room temperature to 100° C. for 6 h to 12 h to form the iron phosphate compound, thereby obtaining the solid-liquid mixture.

3. The preparation method according to claim 1 or 2, characterized in that: The phosphorus source includes one or a combination of phosphoric acid, sodium dihydrogen phosphate, and ferrous dihydrogen phosphate; And / or, the metallic iron includes one or a combination of iron blocks, iron sheets, and iron powder.

4. The preparation method according to claim 1, characterized in that: The acidic regulator includes one or a combination of oxalic acid, tartaric acid, and citric acid; and / or, the carbon source comprises glucose; and / or, the molar ratio of the acidic regulator to the iron element is 1:5 to 1:7.5; and / or, according to the chemical formula Na 3-4.5 Fe 2-3.5 (PO4) 2-2.5 P2O7 adds a sodium source to the solid-liquid mixture; And / or, the amount of the carbon source added satisfies a molar ratio of the carbon source to iron of 1:10 to 1:15; And / or, specifically comprising: mixing the solid-liquid mixture with an acidic regulator, a carbon source, a sodium source and polyethylene glycol and then performing the sand milling, wherein the amount of the polyethylene glycol added is 1 / 400 to 1 / 600 of the total mass of the slurry.

5. The preparation method according to claim 1, characterized in that: Specifically include: The sand milling is performed at a temperature of 20 to 30° C. for 2 to 4 hours, so that the particle size of the particles in the slurry is 500 to 600 nm.

6. The preparation method according to claim 1, characterized in that: The drying is spray drying, the inlet temperature of the spray drying is 210-250°C, and the outlet temperature is 100-105°C.

7. The preparation method according to claim 1, characterized in that: The protective atmosphere is at least one of argon and nitrogen; or, the protective atmosphere is an argon-hydrogen mixed gas or a nitrogen-hydrogen mixed gas, and the volume proportion of hydrogen in the argon-hydrogen mixed gas or the nitrogen-hydrogen mixed gas is 5% to 10%; And / or, the sintering specifically includes: firstly raising the temperature to 290-310°C at a rate of 1.5-2.5°C / min and keeping it warm for 2.5-3.5h, and then raising the temperature to 500-550°C at a rate of 1.5-2.5°C / min and keeping it warm for 8-10h.

8. An iron-based phosphate positive electrode material, characterized in that: It is prepared by the method described in any one of claims 1 to 7.

9. A sodium ion battery positive electrode, characterized in that: The sodium ion battery positive electrode comprises a current collector and a positive electrode active material layer formed on the current collector, wherein the positive electrode active material layer comprises the iron-based phosphate positive electrode material according to claim 8.

10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The positive electrode is the sodium ion battery positive electrode according to claim 9.

Citation Information

Patent Citations

  • Sodium ferric pyrophosphate positive electrode material and preparation method and application thereof

    CN118867197A

  • Sodium ferric phosphate positive electrode material and preparation method thereof, positive electrode and battery

    CN119008875A

  • Sodium ferric phosphate pyrophosphate / C composite material as well as preparation method and application thereof

    CN118117065A

  • Integrated preparation method of anode iron-based phosphate material of secondary battery

    CN119503752A

  • Method for preparing positive electrode material for lithium cell, and lithium cell

    CN1706056A

Cited By

  • Preparation method of composite ferric sodium pyrophosphate material

    CN120172384A

  • A preparation method of composite sodium iron pyrophosphate material

    CN120172384B

  • Composite sodium ferric phosphate positive electrode material, precursor, preparation method of composite sodium ferric phosphate positive electrode material and precursor, and sodium ion battery

    CN120518050A

  • Composite sodium iron phosphate positive electrode material, precursor and preparation method thereof, and sodium ion battery

    CN120518050B

  • KTP type sodium-rich phosphate positive electrode material as well as preparation method and application thereof

    CN120646802A